Effects of environmental variables in coffee production in agroforestry system - Neto, José Nunes Pinto; Alvarenga, Maria Inês Nogueira; Corrêa, Marcelo de Paula; Oliveira, Carla Cristina de (Coffee Science - ISSN 1984-3909, 2014)
The agroforestry systems come up as an alternative for the farmer, by improving productivity, ecological interactions, and environmental quality, in order to control the effects of hail, frost, cold winds etc. In such context, the aim of this study was to check the interference of different levels of shade on the phytomass and microbial biomass parameters and correlate it to the grain production; besides checking the lessening of the Photosynthecally Active Radiation (PAR), by means of measurements carried out above and below the canopy, and compare it to the shade caused by the araucarias as inferred by means of photograph treatment. The study was conducted at a coffee plantation intercropped with araucarias with three different shade levels: Coffee in intense shade (CIS), coffee in regular shade (CRS), and coffee without shade (CWS). Photograph treatment study analysis showed that there was a straight correlation between the lessening of the PAR and the shaded area under the araucarias. In relation to the phytomass, it was observed that the largest quantity occurred in the CIS, which did not differ statistically from the CRS. For the microbial biomass, the highest value was found in the CWS, which did not differ statistically from the CRS. The CRS structure is presented as the most suitable for the cultivation of coffee in terms of available radiation.